Pengaruh Teknik Marmet terhadap Kelancaran Asi pada Ibu Nifas di Uptd Puskesmas Sidodadi - Fifi Ria Ningsih Safari; Eliza Bestari Sinaga; Khairani Purba (STIKes Payung Negeri Pekanbaru, 2023)
Technique Marmet is a technique used to express breast milk. This technique provides a relaxing effect and also reactivates the milk ejection reflex (MER) so that milk begins to drip. Several efforts that can be made to help expedite the expulsion of breast milk in mothers at the beginning of breastfeeding are breast care, oxytocin massage, and the guinea pig technique. This study used a quasi-experimental method (Quasi Experiment). According to the researchers' assumptions, the results of the descriptive analysis showed that the majority of research subjects were carried out using the guinea pig technique, namely 15 people (50.0%) and the majority of research subjects experienced smooth milk production, namely 13 people (43.3%). The results of the chi-square test show that in the 2x2 contingency table, some have an expected value (E) of less than 5, so the p-value used is the Fisher test t_count = 17.875 with a p-value of 0.03. Smaller than 0.05, so it can be concluded that the guinea pig technique has a significant influence on the smooth production of breast milk. In other words, the more regularly the mother performs the guinea pig technique, the greater the chance for smooth milk production for the mother.